2002
DOI: 10.1029/2001jd000654
|View full text |Cite
|
Sign up to set email alerts
|

Exchange fluxes of NO2 and O3 at soil and leaf surfaces in an Amazonian rain forest

Abstract: [1] Trace gas exchange of NO 2 and O 3 at the soil surface of the primary rain forest in Reserva Biológica Jarú (Rondônia, Brazil) was investigated by chamber and gradient methods. The ground resistance to NO 2 and O 3 deposition to soil was quantified for dry and wet surface conditions using dynamic chambers and was found to be fairly constant at 340 ± 110 and 190 ± 70 s m À1 , respectively. For clear-sky conditions, the thermal stratification of the air in the first meter from the forest floor was stable dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 32 publications
(50 reference statements)
5
92
3
Order By: Relevance
“…All tubing and tubing connections that were in contact with the air flow consisted of PFA-Teflon ® (Swagelok, USA). A fan (APC Propellers, USA), which had been coated with Teflon ® by the MPIC mechanical workshop, was installed inside both cuvettes to assure well-mixed conditions in order to reduce the aerodynamic resistance for the trace gas fluxes (Gut et al, 2002). The purified air stream supplied with a certain mixing ratio of O 3 and PAN reached the inner cuvette through the inlet PFA-tube (see Fig.…”
Section: Dynamic Cuvettesmentioning
confidence: 99%
“…All tubing and tubing connections that were in contact with the air flow consisted of PFA-Teflon ® (Swagelok, USA). A fan (APC Propellers, USA), which had been coated with Teflon ® by the MPIC mechanical workshop, was installed inside both cuvettes to assure well-mixed conditions in order to reduce the aerodynamic resistance for the trace gas fluxes (Gut et al, 2002). The purified air stream supplied with a certain mixing ratio of O 3 and PAN reached the inner cuvette through the inlet PFA-tube (see Fig.…”
Section: Dynamic Cuvettesmentioning
confidence: 99%
“…In a greenhouse experiment by Gut et al (2002b) young tropical tree species showed substantial leaf damage (S. Rottenberger, personal communication) after a few days of O 3 fumigation (daytime maximum values of ∼60 ppb). On the other hand, it was recognized, e.g.…”
Section: Ozone Deposition Mechanismsmentioning
confidence: 99%
“…It was estimated on the basis of measurements by Gut et al (2002b), which were performed simultaneously with our flux measurements. D S (z) is the actual deposition to plant surfaces.…”
Section: Ozone Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…It is defined as the time at which the mixing ratio of one of the compounds significantly changes from its initial value when reacting with the other ones. It can also be seen as the time required for reaching a new photostationary state following a change in O 3 , NO or NO 2 mixing ratios, or the reaction rate constants j NO 2 and k 3 (see Ganzeveld et al, 2012 The data gaps in the measured time series of j NO 2 (in s −1 ) above the canopy were filled using the parameterization of j NO 2 as a function of G (in W m −2 ) by Trebs et al (2009). This approach was also used to parameterize in-canopy j NO 2 from a vertical in-canopy profile of G. The latter was calculated as a function of the LAI profile using the method of Monsi and Saeki (1953):…”
Section: Chemical Timescalesmentioning
confidence: 99%